ANALISIS GEOMETRIK PADA TIKUNGAN RUAS JALAN RAYA MAGELANG-KOPENG DAN RAYA SOEKARNO-HATTA (PERTIGAAN CANGUK) - Febri Kurniawan; Sudarno Sudarno (Universitas Tidar, 2018)
Abstract. On Magelang-Kopeng road and Soekarno-Hatta road there has been long traffic jam. This is due to the density of vehicles resulting in accumulation of motor vehicles. In addition, the curves that are at the junction Canguk also too cornering and not meet the standards set by the government. Like a bend with fingers that are too sharp, incomplete slope and curves are in the hill area. The purpose of this study is to analyze the geometry of the bend so that road users can pass safely and comfortably. This research method is done several steps, namely: problem formulation, survey location, data collection, data processing so that obtained the relevant analysis. The results of this study resulted in the calculation that the bends at the Canguk junction Magelang City are planned technically using horizontal alignment with Spiral Circle Spiral type and the required curve bend of 1.91 metres and super elevation must be improved so that road users can pass safely and comfortably.Keyword : geometric, bend, horizontal alignment, analysis